1996
DOI: 10.1186/1297-9686-28-5-415
|View full text |Cite
|
Sign up to set email alerts
|

Body size and developmental temperature in Drosophila simulans: comparison of reaction norms with sympatric Drosophila melanogaster

Abstract: Summary -Reaction norms of two size-related traits (wing and thorax length) were analyzed in relation to growth temperature in a French natural population of Drosophila simulans, using the isofemale lines method. The wing/thorax ratio was also studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
18
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 21 publications
6
18
0
Order By: Relevance
“…Previous investigations, however, demonstrated that the thermal range of Afrotropical D. melanogaster is very close to that of the temperate strains (Cohet et al 1980), so that comparing a European population of this species with the tropical D. ananassae is not a major problem. An interesting point is that thermal tolerance seems to be related to phylogeny: changing the thermal tolerance in Drosophila appears so far to be a difficult evolutionary event, which is clearly observed between distantly related species but not much between allopatrie populations or even sibling species (Cohet et al 1980;David et al 1983;Morin et al 1996). At the individual level, wing and thorax length are positively correlated in all species investigated Barker and Krebs 1995;Morin et al 1996).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous investigations, however, demonstrated that the thermal range of Afrotropical D. melanogaster is very close to that of the temperate strains (Cohet et al 1980), so that comparing a European population of this species with the tropical D. ananassae is not a major problem. An interesting point is that thermal tolerance seems to be related to phylogeny: changing the thermal tolerance in Drosophila appears so far to be a difficult evolutionary event, which is clearly observed between distantly related species but not much between allopatrie populations or even sibling species (Cohet et al 1980;David et al 1983;Morin et al 1996). At the individual level, wing and thorax length are positively correlated in all species investigated Barker and Krebs 1995;Morin et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…An interesting point is that thermal tolerance seems to be related to phylogeny: changing the thermal tolerance in Drosophila appears so far to be a difficult evolutionary event, which is clearly observed between distantly related species but not much between allopatrie populations or even sibling species (Cohet et al 1980;David et al 1983;Morin et al 1996). At the individual level, wing and thorax length are positively correlated in all species investigated Barker and Krebs 1995;Morin et al 1996). Also, when species of very different size are compared, a strong correlation due to an allometric constraint is observed (Reiss 1989): moving a heavier body needs larger wings, but also bigger flight muscles included in a larger thorax.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The polynomial model lends itself directly to plasticity as the direct object of selection. A reaction norm can be studied as a set of coefficients of the polynomial function termed characteristic values (David et al 1994;Morin et al 1996). Evolution of these values furnish clear interpretations about what aspects of plasticity are being selected (Gibert et al 1998a).…”
Section: Discussionmentioning
confidence: 99%
“…Body size in many ectothermic organisms shows a plastic response to temperature, with size increasing under colder developmental temperatures (Alpatov 1930;Ray 1960;von Bertalanffy 1960;Atkinson 1994). This phenomenon has been particularly well documented in Drosophila (David et al 1994Morin et al 1996;James et al 1997;Petavy et al 1997;Azevedo et al 1998;French et al 1998;Imasheva et al 2000;Gibert et al 2004). In addition to plastic responses, evidence from laboratory evolution experiments and clinal studies of geographical populations indicates that temperature can influence the evolution of body size.…”
mentioning
confidence: 96%